Beyond World Images: Belief as Embodied Action in the World. (March 2015) - Strand, Michael; Lizardo, Omar
In this article, we outline the analytic limitations of action theories and interpretive schemes that conceive of beliefs as explicit mental representations linked to a desire-opportunity folk psychology. Drawing on pragmatism and practice theory, we recast the notion of belief as a species of habit, with pre-reflexive anticipation the primary mechanism accounting for both the formation of beliefs and their causal influence on action. We demonstrate the utility of this approach in three ways: first, by linking it with recent research on the cognitive and motor development of infants; second, by drawing out a typology of belief states that accounts for a range of different experiential traits; and third, by applying the new model to reinterpret two belief-based phenomena of broad sociological interest: "irrational" decision making and religious conversion.